2004
DOI: 10.1111/j.0269-283x.2004.00518.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic activities in body and faecal extracts of the storage mite, Acarus farris

Abstract: Trypsin, chymotrypsin, cathepsins B and D, aminopeptidase and carboxypeptidases A and B were detected in body extracts of the storage mite Acarus farris (Oudemans) (Astigmata: Acaridae). Faeces-enriched medium exhibited higher (10-50-fold) specific protease activity rates than those measured with mite body extracts for trypsin, chymotrypsin and carboxypeptidases A and B, suggesting that they are involved in mite digestion. However, the activity of cathepsin B was only three-fold higher in faecal than in body e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Legend: Ã denotes a significant difference from the control based on Tukey's post-hoc comparison at P 5 0.05. explanation because it decreased general proteolytic activity on azocasein. A similar situation was observed in previous studies (Montealegre et al, 2002;Sanchez-Ramos et al, 2004). This event may be interpreted as such: increased cysteine protease activity in mite homogenates does not compensate for the decrease in general proteolytic activity caused by the disruption of disulfide bridges within other proteases, which may inactivate them (Marianayagam et al, 2004).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Legend: Ã denotes a significant difference from the control based on Tukey's post-hoc comparison at P 5 0.05. explanation because it decreased general proteolytic activity on azocasein. A similar situation was observed in previous studies (Montealegre et al, 2002;Sanchez-Ramos et al, 2004). This event may be interpreted as such: increased cysteine protease activity in mite homogenates does not compensate for the decrease in general proteolytic activity caused by the disruption of disulfide bridges within other proteases, which may inactivate them (Marianayagam et al, 2004).…”
Section: Discussionsupporting
confidence: 83%
“…The enzymatic activities of the small peaks at pH 3 suggest the presence of aspartate proteases. Aspartate protease activity has previously been found in A. farris (Sanchez-Ramos et al, 2004), A. siro (Nisbet and Billingsley, 2000), and T. putrescentiae (Ortego et al, 2000). The authors in these previous studies suggested that aspartate proteases in acaridid mites are non-digestive.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Some of them with enzymatic activity included groups 1, 3, 4, 6, 8, 9 and 15 [4, 5]. Other mite species, such as Glycyphagus domesticus [6], Acarus farris [7], Tyrophagus putrescentiae [8], Blomia tropicalis [9, 10], Psoroptes cuniculi [11] and Aleuroglyphus ovatus [12] also contain allergens with enzymatic activity. Serine proteases (trypsin and chymotrypsin) seem to be more abundant in faecal than in whole body extracts [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Other mite species, e.g. Glycyphagus domesticus [9], Acarus farris [10], Tyrophagus putrescentiae [11], Blomia tropicalis [12,13,14], Psoroptes cuniculi [15] and Aleuroglyphus ovatus [16],also contain potent enzymes. Comparative studies have been conducted to analyze the presence of enzymes in mite bodies and spent media.…”
Section: Introductionmentioning
confidence: 99%